The Influence of Organisational Culture on Employee Commitment in Shinyanga Municipal Council, Tanzania - Mwilongo, Nivad; Nkina, Jummanne (Journal of Policy and Leadership, 2025)
Local government Authorities (LGAs) have been vested with the power to ensure the timely and consistent provision of services at the grassroots level. The success of LGAs in meeting their primary goal of serving community members depends on staff commitment and the culture established within each LGA's context. However, existing challenges, such as corruption, turnover and turnover intentions, poor leadership, among others, have been identified as a source of poor service delivery, as they hinder employees' motivation and commitment to serve fellow citizens at the local level. This study examines the influence of organisational culture on employee commitment within Tanzania's local government authorities, focusing on the four typologies defined by the Competing Values Framework: clan, adhocracy, market, and hierarchy. It utilised a structured questionnaire, and 92 employees at the Shinyanga Municipal Council were sampled via stratified random sampling. The responses were considered for analysis using STATA software for inferential statistics, where the Multivariate Multiple Regression (MMR) Analysis was conducted to examine the effect of multiple typologies of organisational culture (clan, adhocracy, market, and hierarchy culture) on multiple dimensions of employee commitment (affective, normative, and continuance). The findings revealed that clan culture and adhocracy culture negatively influence all three dimensions of employees' commitment. In addition, the findings indicated that market culture positively influences all dimensions of employee commitment. Furthermore, the hierarchical culture exerted a positive influence on some dimensions, such as affective and continuance commitment, and a negative influence on normative commitment. The study concluded that organisational culture exerts varied effects on employee commitment, highly dependent on the specific cultural type and the institutional setting. It further recommended that local government authorities create a supportive culture to enhance employee commitment at the local level. This study contributes to the organisational and public administration literature by demonstrating how different types of organisational culture influence employee commitment in distinct ways in Tanzania's LGAs.